PENGARUH PENDIDIKAN PEMAKAI TERHADAP PEMANFAATAN PERPUSTAKAAN DI PERPUSTAKAAN NASIONAL REPUBLIK INDONESIA - Yunita Butar-Butar, Bintang Sandra; Haryanti, Ni Putu Premierita; Ginting, Richard Togaranta (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2020)
ABSTRACT The objective of this research is to inform the user education influences of the advantage of libraries in the Republic of Indonesia National Library. This research uses quantitative methods by using descriptive approach. This research is conducted at the Republic of Indonesia National Library, Central Jakarta. The total of population in this research is 11.542 people and the total of sample is 100 people, that are calculated by using the Slovin formula. This research uses data collection techniques consisting of questionnaires, observation and literature. The data analysis technique used in this study is validity testing, reliability testing and simple linear regression analysis using SPSS software (Social Sciences Statistics Package). The results of this research is tested by the hypothesis testing with sig.t arithmetic <(? = 0.05), it can be concluded that there is a significant influence between user education on library use in the Republic of Indonesia National Library. Keywords : User Education, Library Utilization, National Library